Reactive Separation for Process Intensification and Sustainability - Cardona Alzate, Carlos Ariel; Sanchez, Mariana Ortiz; Andrianovich, Pisarenko Yuri. (Milton : CRC Press LLC, 2019)
This book describes, analyses and discusses the main principles, phenomena and design strategies of reactive separation processes with an emphasis on the intensification as a basis of the sustainability. Different reactive separation processes are explained in detail to show the phenomena and with the purpose of understanding when their use allows advantages based on the output results. Case examples are analysed and the perspective of these processes in the future is discussed. The overall sustainability of reactive separation processes in the industry is also explained separately.
4.4.2 Liquid-Liquid Equilibrium Equation -- 4.4.3 Simulation Procedure -- 4.4.4 Reactive Extraction Process -- 4.4.5 Continuous Process -- 4.4.6 Multistage Reactor Extractor -- 4.4.7 Location of the Biocatalyst Using Magnetic Fields -- 4.4.8 Conclusions -- References -- 5: Reactive Absorption: Uses and Applications, Conceptual Design, Modeling and Simulation, Case Study -- 5.1 Definition -- 5.2 Classification -- 5.3 Advantages and Disadvantages -- 5.4 Uses and Applications -- 5.5 Conceptual Design -- 5.6 Modeling and Simulation -- 5.7 Case Study -- 5.7.1 Considerations and Assumptions
Description based upon print version of record.
5.7.2 Input Data
OCLC-licensed vendor bibliographic record.
Keywords: Separation (Technology); SCIENCE / Chemistry / Industrial & Technical; TECHNOLOGY / Engineering / Chemical & Biochemical